Consumer Preference Towards Fruit in Muara Bangkahulu District, Bengkulu City - Feriyanto Feriyanto; Ketut Sukiyono; Nola Windirah (Badan Penerbitan Fakultas Pertanian (BPFP), 2026)
Preference is a choice of liking or disliking the attributes of fruit available on the market. These attributes are features or equipment attached to the fruit that reflect the nature of the fruit. This research aims to identify the main factors consumers consider when choosing which fruit to consume and to determine consumer preferences based on the attributes of price, quality, size, availability, and vitamin content. This research was conducted in Muara Bangkahulu District, Bengkulu City, from October 2022 to December 2022. The fruits to be studied are green melon, red watermelon, Medan orange, and sweet, fragrant mango. This is because, based on initial observations, this type of fruit is readily available in fruit shops in Muara Bangkahulu District. The analysis in this research uses the AHP (Analytical Hierarchy Process) method. The research results show that the main factor consumers consider when choosing fruit is price, followed by size, quality, availability, and vitamin content. Medan oranges are the main fruit type chosen by consumers based on price, size, and availability. Furthermore, green melons are the main priority for fruit quality, for vitamin content, and, across multi-criteria, Medan oranges are the main choice for consumers.